2017 IEEE International Conference on Communications (ICC) 2017
DOI: 10.1109/icc.2017.7997306
|View full text |Cite
|
Sign up to set email alerts
|

Random caching based cooperative transmission in heterogeneous wireless networks

Abstract: Base station cooperation in heterogeneous wireless networks (HetNets) is a promising approach to improve the network performance, but it also imposes a significant challenge on backhaul. On the other hand, caching at small base stations (SBSs) is considered as an efficient way to reduce backhaul load in HetNets. In this paper, we jointly consider SBS caching and cooperation in a downlink largescale HetNet. We propose two SBS cooperative transmission schemes under random caching at SBSs with the caching distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 27 publications
0
56
0
Order By: Relevance
“…By replacing (23), (24) and (25) in (16), we have derived our approximation¯ M . Note that in case the approximated terms in (11) and (14) were not considered, the derived SCDP in (15) and (16) would write as a non solvable integral which involves a modified Bessel function of the first kind as in [10]. Also, it is known that a closed-form solution for…”
Section: Our Main Resultsmentioning
confidence: 99%
“…By replacing (23), (24) and (25) in (16), we have derived our approximation¯ M . Note that in case the approximated terms in (11) and (14) were not considered, the derived SCDP in (15) and (16) would write as a non solvable integral which involves a modified Bessel function of the first kind as in [10]. Also, it is known that a closed-form solution for…”
Section: Our Main Resultsmentioning
confidence: 99%
“…Each eRRH i ∈ K R is equipped with a cache of size nB i > 0 nats, where B i is the normalized cache size. To provide the spatial file diversity (which can improve the performance of dense wireless networks) [19], each eRRH i ∈ K R randomly prestores nB i nats of nF S nats in the library to its local cache according to certain preferences [20]- [22]. In other words, each eRRH i ∈ K R randomly selects B i /S files from library F at the BBU to store at its local cache.…”
Section: A Cache Modelmentioning
confidence: 99%
“…1) Problem Transformation: In problem (18), equality constraints (16d) and (16e) are two main obstacles for solving it. Fortunately, the researches on equality constraint optimization in [13], [14] have shown that problem (17) can be further reformulated as (19), at the bottom of the next page. In (19a), matrix Ξ s is calculated as (20), at the bottom of the next page, where Φ f,i and Ψ i are Lagrange Multiplier matrices associated with equality constraints (16d) and (16e), respectively.…”
Section: B Inner Optimization Designsmentioning
confidence: 99%
See 2 more Smart Citations